Atividade anti-Pythium insidiosum e toxicidade de mefenoxam e pyraclostrobin - Stibbe, Paula Cristina (2021)
Pythiosis is an infection caused by the oomycete Pythium insidiosum. The disease affects different animal and human species, occurring in various regions of the world. Brazil stands out, with prevalence in animals and Thailand, with prevalence in humans. This infection usually becomes fatal, and does not exist a standard therapy to treat different species affected. The search for different treatment options has already demonstrated in vitro anti-P.insidiosum action of several pharmacological classes, especially antimicrobials. In vivo results, however, are conflicting and each species reacts differently to treatments. In the search for new therapeutic options, this study evaluated two phytoantifungal agents using the broth microdilution technique. Eighteen clinical isolates and three standard strains of P. insidiosum (n=21) were tested against the compounds mefenoxam and pyraclostrobin, in order to verify the susceptibility and define the minimum inhibitory concentration (MIC) and the minimum oomicidal concentration (MOC) of all isolated. In addition, control hyphae of P. insidiosum and hyphae exposed to sublethal concentration of treatment with mefenoxam and pyraclostrobin were evaluated by scanning electron microscopy (SEM) to verify possible structural and morphological differences. Additionally, in vitro toxicity of the compounds on the BALB/c 3T3 cell line and on in vivo experimental model, Caenorhabditis elegans, were evaluated. P. insidiosum isolates presented MICs in the range of 0.625 to 10,000 μg/mL for mefenoxam and 0.019 to 5,000 μg/mL for pyraclostrobin. MOC ranged from 1.250 to 20,000 μg/mL for mefenoxam and 0.039 to 10,000 μg/mL for pyraclostrobin. The images obtained by SEM showed morphological differences between the control hyphae and the hyphae treated with phytoantifungal agents, suggesting the occurrence of structural damage. In vitro and in vivo toxicity tests did not show evidence of toxic effects at the evaluated dosages for both compounds. Finally, the compounds evaluated in this research demonstrate pharmacological potential for effectiveness anti- P.insidiosum, requiring further evaluations in vivo and within multipharmacological therapies.